2017
DOI: 10.1016/j.polgeo.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Interventions in urban geopolitics

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 108 publications
0
26
0
Order By: Relevance
“…Studying how Palestinians in Lydda think and feel about their surveilled districts as well as about the broader landscape of ruins around them resonates with Harb's () recent call for a perspective on ‘the city at war’ focused on people's everyday practices. It also resonates with calls for a ‘domestic urban geopolitics’ (Rokem et al , : 4), and for ‘the analysis of urban geopolitics and everyday life’ (Yacobi, ). I have suggested that urban sociology's conceptual focus on processes of spatial meaning‐making in everyday life offers important insights into developing a perspective on militarized cities that theorizes ‘the quotidian, embodied, and micro‐scale practices that shape urban politics and conflict’ (Fregonese, : 2).…”
Section: Towards An Everyday Perspective On Urban Militarismmentioning
confidence: 63%
“…Studying how Palestinians in Lydda think and feel about their surveilled districts as well as about the broader landscape of ruins around them resonates with Harb's () recent call for a perspective on ‘the city at war’ focused on people's everyday practices. It also resonates with calls for a ‘domestic urban geopolitics’ (Rokem et al , : 4), and for ‘the analysis of urban geopolitics and everyday life’ (Yacobi, ). I have suggested that urban sociology's conceptual focus on processes of spatial meaning‐making in everyday life offers important insights into developing a perspective on militarized cities that theorizes ‘the quotidian, embodied, and micro‐scale practices that shape urban politics and conflict’ (Fregonese, : 2).…”
Section: Towards An Everyday Perspective On Urban Militarismmentioning
confidence: 63%
“…Analytically this implies moving away from the analysis of specific urban and/or development modalities and scales, towards a more open perspective of urbanism as a 'relational site' shaped through the engagements of different actors and claims making practices [13]. It is here where the novel framework of 'urban geopolitics' is particularly well suited, which has recently been put forward by political geographers Rokem et al and Rokem & Boano, which have sought to centre urban debates on everyday struggles over urban space [12,13]. The basic premise of urban geopolitics is that the control of urban space is inherently contentious and that these contentions should be brought to the foreground.…”
Section: From Development and Urbanism To Urban Geopoliticsmentioning
confidence: 99%
“…The article begins with a concise discussion of contemporary debates on African urban development and urbanism, leading into a framework of 'urban geopolitics' centred on the everyday struggles over urban space [12,13]. This is then followed by a historical analysis of Beira's city, detailing an urban trajectory shaped through the rise and fall of (hostile) state regimes and broader global geopolitical shifts.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of urban geopolitics has therefore been to produce new insights on the fascinating yet potentially treacherous relationship between violent geopolitical processes and urban space (see, e.g. Rokem et al 2017).…”
Section: On the Concept Of City Geopoliticsmentioning
confidence: 99%